Analisis Kadar Merkuri (Hg) Pada Rambut Penduduk Desa Kayeli, Akibat Penambangan Emas Tanpa Ijin di Areal Gunung Botak , Kab. Buru-Provinsi Maluku - Rumatoras, Hadijah; Taipabu, Muhammad I.; Lesiela, Lewi; Male, Yusthinus T (Indonesian Journal of Chemical Research, 2016)
In November 2011, the gold mining activities in Botak Mountain, Buru island more increase and it has used mercury as a main ingredient in the extraction process. The use of mercury in the gold mining on Botak Mountain is done freely by the miners (people), allowing mercury waste wasted together distributed to the environment. With the distribution of gold mining in the area of waste water, then allow mercury can accumulate in human through the food chain. This research aims to determine accumulation of mercury at hair of Kayeli Villagers. The research method is used survey and analyze. In this research, were used observation, field sampling and laboratory analyze. The result showed that concentration of mercury analyzed at villagers’s hair is 0.10-3.25 ppm. Based on the result, concentration of mercury analyzed at villagers’s hair has exceeded standard of mercury limits, i.e 0.05 ppm.